The successful implementation of key performance indicator system in a telecommunications company - Hassan, Shahizan; Li, Feng; Sahak, Muhammad Firdaus; Perumal, Manivannan; Ab Ghani, Mohd Yusoff (Othman Yeop Abdullah (OYA) Graduate School of Business, Universiti Utara Malaysia, 2014)
Despite technological advances and extensive research, system implementation failure is still the cause of concern for many business organisations.Hence these organisations could learn from many examples of success stories in the information system implementations.This paper presents a case study of the successful implementation of a KPI System called KPIS-NE, by Nada Suria Co., Ltd. The main focus would be to understand the purpose of the system, how it was developed, what is the technological infrastructure needed to implement it, and what is the impact of its implementation on the company and its employees.The system was introduced to promote a culture of performance in NS and to ensure a transparent performance appraisal. It is a secure webbased system which is accessible anywhere and anytime.The development of KPIS-NE was based on the Waterfall System Development Methodology.To ensure the system’s efficiency and eff ectiveness, KPIS-NE was pilot-tested for a period of 6 months.Upon completion, a study was conducted using interview and document analysis methods to assess the system’s success.The feedback shows that the system has garnered positive responses from the employees and the system’s owner despite the existence of several issues and challenges that need to be addressed.